Implementation of Discussion Method to Improve Student Learning Outcomes in Islamic Education at SMA Negeri 2 Padang - Gusmaneli (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve student learning outcomes in Islamic education learning using the Discussion Method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure the improvement of student learning outcomes in Islamic education learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning using the Discussion Learning Method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of completeness of improving student learning outcomes in each cycle with details of the pre-cycle 48.56%, the first cycle 69.47% and in the second cycle increased to 90.57%. Thus, the use of the Discussion Learning Method can be used as an alternative to increase student activity in Islamic education learning in Islamic religious education learning.